Development and Validation of Analytical Method for Quantitative Estimation of Miglitol and Metformin in Combined Dosage Form - Sejal R Patel, Prachi V Kabra, Ritu V Kimbahune, Ravikiran Markad, LVG Nargund (Journal of Applied Pharmaceutical Science)
A simple, accurate, economical and reproducible UV spectrophotometric method for simultaneous estimation of Miglitol and Metformin in combined tablet dosage form has been developed. The developed method employs multi component spectroscopy using 300nm, 270nm, 240nm and 210nm as wavelengths for estimation. Miglitol and Metformin were found to be linear in the concentration range of 0.2-1.2 µg/ml and 2-12 µg/ml respectively. %Assay was found to be in the range of 99.27 – 99.92% and 99.29 – 99.97% for Miglitol and Metformin respectively. Results of analysis were validated statistically in accordance with ICH guidelines.
Keywords: Miglitol,Metformin,Multi Component Spectroscopy.